Studi Komparatif Kadar Gula Darah Puasa Pada Lansia Hipertensi Dengan Non Hipertensi Di Balai Pelayanan Sosial Tresna Werdha Yogyakarta Unit Abiyoso. - Santi Damayanti (Indonesian Journal of Nursing Scientific, 2022)
Hypertension is a disease that usually occurs in adults and the elderly. Hypertension in the long term causes various complications, one of which can make cells insensitive to insulin which interferes with blood sugar levels. Patients with hypertension who take hypertension drugs will also increase the risk of developing diabetes mellitus. The aim of the study was to determine the differences in fasting blood sugar levels in the elderly with hypertension and without hypertension at the Tresna Werdha Social Service Center, Abiyoso Unit, Yogyakarta. This research method is a comparative study with a cross-sectional design. The sample size for the hypertension group is 30 people and the non-hypertensive is 30 people. The sampling technique usethe d purposive sampling method. Data analysis with Independent T-Test test. The average fasting blood sugar in hypertensive elderly is 107.77 mg/dl and 90.57 mg/dl without hypertension. Statistical results using the Independent T-Test test obtained a P value of 0.025 (P count <0.05), with an OR value of 21.36 with a 95% confidence level. There is a Difference in Fasting Blood Sugar Levels in Hypertensive and Non-Hypertensive Elderly at Tresna Werdha Yogyakarta Social Service Center, Abiyoso Unit. Elderly with hypertension need to have regular fasting blood sugar checks to identify diabetes as early as possible.